PROFIT/LOSS ANALYSIS (Case Study of Ibu Wiyono's Peanut Cracker Agroindustry in Rimbo Bujang District, Tebo Regency) - Muhammad Padli; Supriyono Supriyono; Widuri Susilawati (Baselang, 2022)
ABSTRACTThe purpose of this study was to analyze the profit/loss of Ms. Wiyono's peanut-cracker agro-industry and to analyze the business efficiency of Mrs. Wiyono's household-scale peanut-cracked agro-industry. This research was carried out in Rimbo Bujang District, Tebo Regency. The research method used is a survey research method, the object of research is the existing Peyek Peanut agroindustry, with a research time of one month which will be carried out on January 1, 2020 to January 30, 2020. The type of research used is quantitative research, while the data sources used are quantitative research. used, namely primary data and secondary data. The data analysis used in this study is an analysis of profit and loss, total revenue and profits as well as business efficiency of peanut curd. The results showed that, Mrs. Wiyono's Peanut Crack Business in one production period with a total cost of RP. 4,390,500. Generate revenue of Rp. 8,600,000 with a total income of Rp. 4,209,500. In other words, Mrs. Wiyono's Peanut Cracker agro-industry business is profitable and feasible to be developed and the income received from the value of the revenue-to-cost ratio (R/C ratio) Ms. Wiyono's peanut-cracker business is 1.95, this shows that the revenue-to-cost (R/C ratio) C ratio) of 1.95 can be interpreted for every Rp. 1 of the costs incurred, the peanut cracker business provides an income of Rp. 1.95. The value of the R/C ratio of Mrs. Wiyono's peanut-crack agro-industry in Rimbo Bujang District is efficient.Keywords: Business Analysis, Efficiency and Nuts